2012
DOI: 10.1507/endocrj.ej11-0258
|View full text |Cite
|
Sign up to set email alerts
|

Familial short stature with IGF-I receptor gene anomaly [Review]

Abstract: Abstract. Type I insulin-like growth factor receptor (IGF-IR) is widely expressed across many cell types in fetal and postnatal tissues. The activation of this receptor after the binding of secreted IGF-I and IGF-II promotes cell differentiation and proliferation. IGF-IR has an important role in normal fetal and postnatal growth and development. IGF-IR gene anomalies presenting with intrauterine and postnatal growth retardation have recently been reported in some families. Familial short stature with IGF-IR ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…These patients are phenotypically distinct from the patients with the IGF-1 gene mutation described by Woods et al [36]. IGF-1R gene variants, including heterozygous IGF-1R mutations or haploinsufficiency of this gene, should be investigated in subjects with FSS [38]. …”
Section: Etiology and Classificationmentioning
confidence: 99%
“…These patients are phenotypically distinct from the patients with the IGF-1 gene mutation described by Woods et al [36]. IGF-1R gene variants, including heterozygous IGF-1R mutations or haploinsufficiency of this gene, should be investigated in subjects with FSS [38]. …”
Section: Etiology and Classificationmentioning
confidence: 99%
“…Mice with a homozygous deletion of the gene encoding the IGF-I high affinity receptor ( Igf1r ) show a delayed ossification in the cranial and facial bones, inner ear alterations and die shortly after birth [10], [11]. Furthermore, partial deletion of the Igf1r gene causes postnatal growth retardation in humans [12]. IGF1R activation recruits insulin receptor substrates (IRS).…”
Section: Introductionmentioning
confidence: 99%
“…The first human IGF-1R mutation was discovered during the screening of SGA in Germany and the US in 2003. Many clinical studies have shown that IGF-1R gene mutations were related to short stature (Yu, 2011;Kawashima et al, 2012), such as SGA and intrauterine growth retardation (Klammt et al, 2008). Phenomena such as insensitivity to GH and IGF-1 resistance have been found in ISS patients (Cohen et al, 2010), which suggested that ISS might be related to IGF-1R gene abnormalities.…”
Section: Discussionmentioning
confidence: 99%